(untitled) (Research, Society and Development, 2022)
The rising cost of commercial fertilizers and increasing environmental pollution make the use of organic waste in agriculture an attractive option from an economic point of view due to carbon and nutrient cycling. Thus, composting appears as an efficient way to obtain the controlled biodegradation of organic waste. In this sense, the present work aimed to analyze the behavior of temperature during the composting process of different types of materials, agro-industrial and agroforestry residues. The experiment was carried out at the Universidade Federal Rural da Amazônia - UFRA, Parauapebas campus between October 30, 2018 and January 30, 2019, the compost piles were assembled in the seedling nursery, an open shed with shade cover. The materials of the first compost bin (Leira 1) were untanned bovine manure + sugarcane bagasse + vegetable remains + sawdust. The second composter (Leira 2) is untanned bovine manure + litter + sawdust. It was possible to observe that in the first 3 days the temperature of the first Compost (Leira 1) rose rapidly, characterizing the beginning of microbial activity. Over the 90 days, the piles presented odor due to areas with excess water and consequent anaerobic disease, that is, excess water did not allow the passage of oxygen in the compost. In the first stage of the second composting process (Leira 2) the maximum temperature reached was 32°C on the 14th day. Composting is an alternative that deserves visibility as an economically viable and environmentally sustainable alternative.